LEGAL ASPECTS OF USING OF CLOUD TECHNOLOGIES - Юдін, О. К.; Зюбіна, Р. В. (Science-based technologies, 2014)
Analysis of cloud technologies in different countries has been conducted. Definitions of the «cloud computing» term in Russia, Europe, USA and Ukraine are defined. The operation of this technology can provide rapid development of the administration of public information resources are defined. However, today there is no legal framework and were not created special rules or laws that regulate all matters relating to the use of cloud technologies in various fields of information society are noted.The implementation of all technological and social potential of cloud technology requires cooperation between government, industry and private users, namely among all subjects of information relations. This paper outlines the problems of interaction between cloud service provider and use, formed on the basis of providing the information needs of the country. Ways of improving the legal framework of Ukrainian legislation are defined.